Managing Changes in First Nations’ Health Care Needs: Is Telehealth the Answer? - Lavoie, Josée Gabrielle; Williams, Donna (The Journal of Community Informatics, 2009)
The health care needs of First Nations are changing. Chronic diseases now account for most hospital admissions, partially as a result of underinvestment in primary health care. This situation results in an unnecessary reliance on secondary and tertiary care, at a must higher cost to the provincial health care systems, and human cost to First Nations themselves. Telehealth is being promoted as a possible solution. This remains under-researched. While cost savings related to transportation have been documented, researchers have yet to tackle potential efficiencies across the federal/provincial health system divide. Les besoins des Premières nations en matières de services de santé sont en transition. Les maladies chroniques constituent la majorité des admissions dans les hôpitaux, en partie due à un manque d’investissement dans les soins de santé primaires. Cette situation résulte en une dépendance envers les services de santé secondaires et tertiaires, et engendre des coûts additionnels pour les systèmes de santé provinciaux, ainsi que des coûts humains considérables pour les Premières nations. Télésanté est maintenant promu comme une solution possible. Alors que des économies en terme de transport ont été documentées, la recherche ne s’est pas penchée sur les efficacités potentielles à réaliser à travers les systèmes fédéraux et provinciaux.